A case of severe retroperitoneal chyle leakage and subsequent chylothorax secondary to partial laparoscopic nephrectomy - Lu Ping; Chuhan Wang; Haoran Huang; Runmeng Cui; Jian Cao; Jie Dong (Urology Case Reports)
Retroperitoneal chyle leakage combined with chylothorax after nephrectomy is rare in clinical practice. We report a 41-year-old female who developed severe chyloretroperitoneum along with subsequent chylothorax after partial nephrectomy. The patient underwent nutritional control, received octreotide treatment and had a complete recovery after 58 days. A damage to the cisterna chylic could account for the leakage. The chylothorax was a displacement through the diaphragmatic hiatus. Comprehensive review showed that near 30 % of such patients would require re-surgery or interventional treatment. The current case stresses the importance of careful examination, timely diagnostic test and appropriate treatment of abnormal drainage after nephrectomy.